Modeling the shape of tool wear during cutting of the composite materials - Khavin, G. L. (Національний технічний університет "Харківський політехнічний інститут", 2021)
The process of the shape changing for the tool cutting edge in relation to the initial state due to wear during cutting of polymer composite materials is considered. Modern experimental achievements in the study of the nature of changes in microgeometry in the process of wear are analyzed. Based on the analysis of experimental data, an assumption was made about a slight change in the initial rake angle and the rounding radius of the tool tip during wear. On this basis, a conclusion was made about the one-parameter nature of the change in the geometry of the tool cutting edge in the process of interaction with the composite. A model for removing the volume of material is proposed, which makes it possible to determine the total loss of weight of the tool during the cutting process. The relationship between flank wear, dimensional wear and change in tool weight is shown. A geometric model is used to determine weight loss. The proposed assumptions in the mathematical model are discussed. As a first approximation in the calculations, a simplified definition of the worn area near the tool tip is proposed. A generalized algorithm for step-by-step calculation of the tool tip geometry and the inverse problem of weight loss during operation are considered.

Розглянуто процес зміни форми ріжучої кромки інструменту по відношенню до початкового стану за рахунок зношування при різанні полімерних композиційних матеріалів. Проаналізовано сучасні експериментальні досягнення в дослідженні характеру зміни мікрогеометрії в процесі зношування. На основі аналізу експериментальних даних зроблено припущення про незначну зміну початкового переднього кута і радіуса округлення вершини інструменту в процесі зношування. На цій підставі зроблено висновок про однопараметричний характер зміни геометрії різальної крайки інструмента в процесі взаємодії з композитом. Запропоновано модель видалення обсягу матеріалу, що дозволяє визначити загальну втрату ваги інструменту в процесі різання. Показано взаємозв'язок зносу по задній поверхні, розмірного зносу і зміни ваги інструменту. Для визначення втрати ваги використовується геометрична модель. Обговорюються запропоновані допущення в математичній моделі. В якості першого наближення при проведенні обчислень запропоновано спрощене визначення зношеної площі біля вершини інструменту. Розглянуто узагальнений алгоритм покрокового обчислення геометрії вершини інструменту і зворотна задача втрати ваги за час роботи.
Моделювання форми зношування інструменту при різанні композиційних матеріалів
Keywords: cutting of composites; geometric model; microgeometry of the cutting edge; flank wear; mathematical model; weight loss of the instrument; різання композитів; втрата ваги інструменту; мікрогеометрія ріжучої кромки; знос по задній поверхні